Efektivitas Penerapan Social Media Marketing Pada Brand Awareness Produk Crafting UMKM Kota Malang - Krismi Budi Sienatra; Brigitta Maryellen Salecius; Sri Nathasya br Sitepu; Devi Rahnjen Wijayadne; Irantha Hendrika Kenang (Jurnal Bisnis Inovatif dan Digital, 2025)
This study is to find out how using Instagram for digital marketing affects the rise in brand recognition among small businesses that make things in Malang City. This study uses a quasi-experimental design with both a control group and an experimental group. It then analyzes the data using the Wilcoxon Signed-Rank Test. The study's results demonstrate that digital marketing methods led to a big rise in all measures of brand awareness, such as recall, recognition, purchase, and consumption. The p-value from the difference test shows that social media marketing works to make people more aware of your brand. This study argues that small and medium-sized businesses (SMEs) should make the most of Instagram to improve their marketing and engagement.